2011
DOI: 10.1200/jco.2010.34.1552
|View full text |Cite
|
Sign up to set email alerts
|

Completion of Adjuvant Chemotherapy and Use of Health Services for Older Women With Epithelial Ovarian Cancer

Abstract: There is considerable room for improvement in helping older patients with ovarian cancer initiate and complete chemotherapy. The oldest women who completed chemotherapy in this study did not use health services more than younger women did. Treatment teams for older patients with ovarian cancer should include expertise in geriatric assessment, should carefully identify medical and psychosocial barriers to completing treatment, and should support patients throughout treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Chemotherapy feasibility rates were consistent with previous studies, which ranged from 49.1% [19,20,23,43,[45][46][47][48] to 80% [49]. The highest feasibility rates were found in studies [19,20,49] that included only patients without metastases, whose functional status was probably better than in our population.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Chemotherapy feasibility rates were consistent with previous studies, which ranged from 49.1% [19,20,23,43,[45][46][47][48] to 80% [49]. The highest feasibility rates were found in studies [19,20,49] that included only patients without metastases, whose functional status was probably better than in our population.…”
Section: Discussionsupporting
confidence: 79%
“…Definitions of feasibility vary widely, particularly for surgery and chemotherapy [19,20,23,24,43,[45][46][47][48]. Surgery feasibility has been defined as successful completion of the planned surgical procedure, tumor-free resection margins, or absence of postoperative complications with survival on day 30.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, older adults are less likely to receive the most effective cancer treatments 2 and to complete a standard course of chemotherapy (CTX). 3 To optimize the receipt of cancer treatments in older adults, a significant amount of research has focused on predictors of mortality, dose reductions, and other traditional treatment outcomes (for reviews see 4–7). While prediction of these treatment outcomes is important, 8 virtually nothing is known about the impact of CTX on older oncology patients’ functional status during the receipt of CTX.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that the quality of chemotherapy for ovarian cancer is highly variable; chemotherapy is frequently omitted when indicated or delivered in a suboptimal manner. 27,28 Going forward, strategies to optimize adjuvant chemotherapy for women with ovarian cancer are clearly needed.…”
Section: Discussionmentioning
confidence: 99%